Working Characteristics Simulation of p+-CuO / p-ZnTe / n-CdSe / n-MoSe2 / Mo Solar Cell - A.S. Opanasyuk; M.M. Ivashchenko; I.P. Buryk; V.A. Moroz (Журнал нано- та електронної фізики)
In this paper it was carried out the simulation of the main working characteristics (light I-V curves, quantum yield spectral dependencies) of CuO / ZnTe / CdSe / MoSe2 / Mo solar cell (SC). As a study result there were determined open-circuit voltage UOC, short-circuit current density JSC, fill-factor FF, and the device’s efficiency depending on its constructive features (window, absorber and per-contact layers thickness) and working temperature. There were estimated SC’s parameters with the maximum conversion efficiency of solar energy.